STRATEGI PEMASARAN KOMUNIKASI DIGITAL MARKETING PLATFORM (CASHBAC) UNTUK MENINGKATKAN DAYA BELI KONSUMEN - Katrina Katrin; Zon Vanel (SOURCE : Jurnal Ilmu Komunikasi, 2020)
This research is focused on communication marketing strategies at PT. Global Pay Indonesia (Cashbac). The purpose of this research is to find out the marketing strategy of digital marketing platform (Cashbac) to increase consumer purchasing power. The main theory is Marketing Mix (4P). The object of this research is the communication marketing strategy by the sales team and the Marketing team at PT. Global Pay Indonesia (Cashbac). The research method used is qualitative with a case study approach. The results of this study are that Cashbac has run all four aspects of prices, places, products and also promotions to increase consumer purchasing power from time to time to be even higher.